Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1097/00007890-200112270-00016
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Chemokines and Chemokine Receptors Shapes the Inflammatory Response in Rejecting Human Liver Transplants1

Abstract: The patterns of chemokine expression in liver allografts during rejection suggest that the recruitment and positioning of lymphocytes is mediated by specific chemokines. Although ligands for the receptors CXCR3 and CCR5 are important for recruitment, the restriction of SDF to bile ducts suggests that CXCR4 may be involved in the retention of alloactivated lymphocytes at sites of graft damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 40 publications
3
114
3
Order By: Relevance
“…The present study demonstrated enhanced SDF-1 expression on BEC in diseased livers compared with that in normal liver, although the previous report showed SDF-1 expression on BEC in the normal liver as well as livers undergoing rejection (Goddard et al, 2001). A low level of expression may exist on BEC in the normal liver, as the message is demonstrated in the normal liver.…”
Section: Scdf-1 In Liver Diseasescontrasting
confidence: 88%
See 1 more Smart Citation
“…The present study demonstrated enhanced SDF-1 expression on BEC in diseased livers compared with that in normal liver, although the previous report showed SDF-1 expression on BEC in the normal liver as well as livers undergoing rejection (Goddard et al, 2001). A low level of expression may exist on BEC in the normal liver, as the message is demonstrated in the normal liver.…”
Section: Scdf-1 In Liver Diseasescontrasting
confidence: 88%
“…These results suggest that each pair of combination recruits a distinct lymphocyte subpopulation into a specific compartment in the liver. This is supported by the recent findings that differential expression of chemokines and chemokine receptors shape inflammatory response in the rejecting human liver transplant (Goddard et al, 2001). …”
Section: Terada Et Alsupporting
confidence: 58%
“…This expression may be enhanced during the development of inflammatory liver diseases such as chronic hepatitis C and alcoholic hepatitis, 18,48 and may also be increased in both acute and chronic liver allograft rejection. 49 The results of the current study suggest that the immunosurveillance role played by CCR5-positive lymphocytes may be compromised under special circumstances. These may include reduced CCR5 expression, a potential increase in antigenic load within the portal vein associated with colonic inflammation and the presence of other modifying genes that push the response towards inflammation and fibrosis rather than resolution.…”
Section: Discussionmentioning
confidence: 70%
“…22,23 Furthermore, others have demonstrated that increased expression of CXCL10 is associated with accelerated progression of inflammatory liver disease suggesting that CXCR3 is an important receptor in regulating chronic liver inflammation. 38,39 Studies in diverse tissues including the brain, liver, and lung suggest that CXCR3 does not provide a tissue-specific signal for lymphocyte recruitment but is associated with infiltration of inflamed tissues regardless of the anatomical site.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Moreover CXCR3 ligands are up-regulated on hepatic endothelium at sites of T-cell infiltration in chronic hepatitis and their presence has been correlated with outcome of inflammatory liver disease. 24 -27 We have developed a flow-based adhesion assay using human hepatic endothelium which allows us to model leukocyte interactions with hepatic endothelium under physiological conditions of blood flow.…”
mentioning
confidence: 99%